Using "Hot Seating Strategy" to Teach a Descriptive Text in Senior High School - Pertiwi Putri Primayadi; Yetti Zainil (Journal of English Language Teaching, 2018)
Based on the writer’s experience, many students have difficulties in speaking, especially descriptive text. Considering this problem, an alternative teaching strategy is needed to help students improve their speaking skill in terms of describing something. That is why this paper is conducted. It is aimed at explaining how to use an educational drama game which is called hot seating strategy in teaching spoken descriptive text to senior high school students. Before implementing this strategy, the teacher needs to prepare a “hot seat”. Hot seating strategy is conducted by dividing students into several groups of four or five. After that, the teacher takes the hot seat and puts it in front of the class. Then, one representative member of the group sits on the hot seat, not facing the board. Next, the teacher writes down the name of people, tourism places or famous historical places on the board. The members facing the board have to describe the words written on the board. Finally, the one on the hot seat guesses what is being described. It is believed that this strategy can help many students improve their speaking skill in describing something.Key words: speaking, descriptive text, hot seating strategy.